Диэлектрические потери в контрольных кабелях различных зон атомных электростанций - Федяй, А. С. (НТУ "ХПИ", 2016)
Состояние образцов кабелей, эксплуатируемых в различных зонах атомных электростанций, а также, образцов, хранившихся на складе, оценивается путем измерения тангенсов углов диэлектрических потерь изоляционных промежутков. Указанные параметры отличаются для кабелей, находившихся в разных условиях эксплуатации. Измеряя tgδ после ускоренного радиационно-термического старения и увлажнения можно выявить процессы старения изоляции кабелей.

In the nuclear reactor control system of heat and energy release of nuclear power plantsused radiation-resistant control cables with XLPE insulation. Monitoring of the technical condition of the cables is important for safety. It is proposed to control condition of the cablesby measuring the dielectric loss tangent of angles insulation spaces samples cables, which are selected from different parts of the cable ducts. Cables that are located in different areas of a nuclear reactor grows old differently. Thus, samples of cables germozone aged more than cable samples from clean zone Accordingly, the different angles of the dielectric loss tangent for the cables that were in different conditions. Measuring tgδ after accelerated aging of radiation-thermal and moisture can reveal aging of cable insulation.
Dielectric losses in the different zones of control cables nuclear power plant
Keywords: внутриреакторный контроль; тангенс угла; ускоренное старение; изоляция кабелей; влагокамер; control cables; nuclear power plants; dielectric loss tangent; accelerated aging; insulation